2012
DOI: 10.1186/1556-276x-7-538
|View full text |Cite
|
Sign up to set email alerts
|

Donor impurity-related linear and nonlinear intraband optical absorption coefficients in quantum ring: effects of applied electric field and hydrostatic pressure

Abstract: The linear and nonlinear intraband optical absorption coefficients in GaAs three-dimensional single quantum rings are investigated. Taking into account the combined effects of hydrostatic pressure and electric field, applied along the growth direction of the heterostructure, the energies of the ground and first excited states of a donor impurity have been found using the effective mass approximation and a variational method. The energies of these states are examined as functions of the dimensions of the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Most of those investigations were made for spherical quantum dots systems (see for instance Refs. [9,40,41]) and there are also works on single quantum rings structures [20,42,43]. In our case, the nonlinear coefficient function on photon energy contributes to the clearly observable shift of the total absorption coefficient maximum value from the corresponding threshold energy point and to the nonmonotonic behavior of absorption strength as the function of L 2 .…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…Most of those investigations were made for spherical quantum dots systems (see for instance Refs. [9,40,41]) and there are also works on single quantum rings structures [20,42,43]. In our case, the nonlinear coefficient function on photon energy contributes to the clearly observable shift of the total absorption coefficient maximum value from the corresponding threshold energy point and to the nonmonotonic behavior of absorption strength as the function of L 2 .…”
Section: Resultsmentioning
confidence: 56%
“…All this leads to conclude that the features of the donor impurity complex in a unique geometry like the concentric double QRs conditions this particular optical response whose physical reason lies on the magnitude of the expected intra-and inter-state values of the electric dipole moment. These authors have not found in the literature a similar behavior of the nonlinear optical absorption coefficient in reports involving nonlinear impurity-related absorption [9,20,40]. Most of those investigations were made for spherical quantum dots systems (see for instance Refs.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Estudios recientes han reportado el coeficiente de absorción óptica intrabanda lineal y no lineal en anillos cuánticos de GaAs aislados bajo los efectos de presión hidrostática y campo eléctrico (Barseghyan, et al, 2012). Entre los resultados arrojados en dicha investigación está que la variación de los diferentes tamaños característicos de la geometría de la estructura puede generar corrimientos bien sea al rojo o al azul de los picos resonantes del espectro óptico intrabanda.…”
Section: Introductionunclassified